Analysis of elimination half-lives in MamTKDB 1.0 related to bioaccumulation: Requirement of repeated administration and blood plasma values underrepresent tissues. (October 2021) - Hofer, Tim; Myhre, Oddvar; Peltola-Thies, Johanna; Hirmann, Doris
Highlights: MamTKDB 1.0 allows investigation on how chemical properties influence elim t1/2. Generation of representative elim t1/2 requires repeated administration. Blood plasma elim t1/2 underrepresent those in tissues. In humans, elim t1/2 for PCBs increases with the degree of chlorination. MamTKDB 1.0 is a promising database for bioaccumulation assessment of chemicals. Abstract: When building the novel public mammalian toxicokinetic database (MamTKDB) we collected and included 3927 elimination half-lives ( elim t1/2 ) for 1407 xenobiotics in various species (rat, human, mouse, dog, monkey, rabbit, cattle, pig, sheep, guinea pig, hamster, horse and goat) with specification of compartment (whole body, organ/tissue, cell type, medium) studied. Here we describe and analyse the collected data in MamTKDB 1.0. Most elim t1/2 are for humans and rats and their data differ in some ways: whereas the rat data are mainly for pesticides, the human data are mainly for pharmaceuticals and environmental contaminants. There are also differences in types of compartments studied and in metabolites followed: human elim t1/2 are mainly whole body based (i.e. based on blood plasma or excretion), animal data are additionally for various organs/tissues, cells or media. Contrary to human studies, animal studies regularly administrate radiolabeled (e.g. 14 C) substances and distribution of both parent and eventual metabolites are followed, measuring the radioactivity. In rats, substances had been given through single, preconditioning or repeated administration. Single administration studies dominated, but repeated studies generally had longer elim t1/2 than single or preconditioning studies for which elim t1/2 were similar. Repeated administration studies should better ascertain steady state conditions throughout the body, a process involving time-dependent tissue loading, and the data show that for most substances, repeated studies are required to address bioaccumulation potential. About 65% of the substances in MamTKDB 1.0 fulfilled the octanol–water and octanol–air partitioning-based screening criteria (log Kow  > 2 and log Koa  > 5) for further bioaccumulation assessment and/or testing, and most of the substances with long elim t1/2 in both humans and rats fulfill these criteria. Of note, however, there are also many chemicals with log Kow  > 2 with intermediate or short elim t1/2 . Per- and polyfluoroalkyl substances (PFAS) stand out in that they often have log Koa  < 5. Rats are poor toxicokinetic test models for perfluoroalkyl acids (PFAAs) for which pigs (and possibly mice) elim t1/2 data resemble those of humans better. Perfluorinated carboxylic acids (PFCAs) and perfluorinated sulfonic acids (PFSAs) of similar molecular weight had similar elim t1/2 in the species tested. For polychlorinated biphenyls (PCBs), elim t1/2 increases with the degree of chlorination in humans. In relation to other compartments, blood plasma/serum had among the shortest elim t1/2 in rats and often underrepresent elim t1/2 in tissues. Rat data were divided into 38 compartment (tissue or media) types out of which 20 had sufficient data for correlational tests. In general, there was a strong degree of correlation of rat elim t1/2 in-between most compartments, but there were also exceptions. Surprisingly, the correlation between brain and white fat was relatively weak. Interestingly, several substances or their metabolites bound to haemoglobin in red blood cells. MamTKDB 1.0 allows investigation on how certain chemical characteristics influence elim t1/2 and is a promising database for assessment of bioaccumulation potential.